Study of Cephalic Index and its correlation with Sex and Race in Central India - Keche, AS; Keche, HA; Sahoo, N; Thute, PP; Fulmali , DG (Journal of Indian Academy of Forensic Medicine, 2024)
The technique of expressing quantitatively the form of the human body, living or dead and also skeleton is anthropometry. In the world, all human beings belong to the same species, Homo sapiens. Any two individuals are not the same in all their measurable traits, even there are differences in the genetically identical twins in some respects. For estimating sex and race, cephalofacial measurements and indices are useful like the cephalic index or cranial index. 3-4 racial groups are organized by anthropologists based on skull categorization methods. India falls in this craniofacial measurements group’s as considered by Thomas Huxley. Asian skulls are brachycephalic with wide faces having flat supranasal regions and facial flatness. Craniofacial type of Australoids fall between Negroids and Caucasoids. The study was conducted on 196 medical students (92 males and 104 females). Hardlika’s method was used to measure the cephalic index. The mean cephalic index was 79.71 ± 4.55 in males and in females it was 83.14 ± 7.69. Irrespective of gender the mean cephalic index of overall study was found to be 81.53 ± 6.62. Based on cephalic index, 45.65% males were dolicocephalic, 31.52% mesocephalic, 15.22% brachycephalic and 7.61% hyperbrachycephalic. In females, 46.15% were dolicocephalic, 33.65% mesocephalic, 10.58% brachycephalic and 9.62% hyperbrachycephalic.